(untitled) (International Journal of Architecture and Urbanism, 2020)
Business Hotel and Shopping Mall are buildings that used as a place to stay, especially for those who in a business trip and grocery facility for guests in the hotel and people around. The exists of hotel and mall in an area usually can attract people to visit that area and used as a place to rest and to gather, this is the main reason on choosing Hotel and Mall to be one of the facilities in supporting area of Science and Technopark in campus USU Kwala Bekala. Based on the USU Kwala Bekala masterplan, the site with 1,6 Ha area is located in the entrance zone, which is the gateway area of USU Kwala Bekala, so that the concept of the mass was building as a gate. This building is expected to be one of the areas that can integrate users with all of the facilities in Science & Techno Park of Campus USU Kwala Bekala. From the analysis that has done, the final design was the buildings are separated into two mass and connected with a sky bridge with the implementation of green architecture. The application of this concept seen in the use of windows, skylight, and the inner court as natural lighting and ventilation, roof garden to recycle rainwater, and secondary skin as a sunlight buffer. These applications are expected to help in reducing the use of water and electricity.